Między preliminariami a traktatem pokojowym – obraz Rosji bolszewickiej na łamach „Robotnika” w okresie od 12 X 1920 do 18 III 1921 r. - Grabski, Maciej (Instytut Historii PAN, 2024)
The article presents a picture of the Polish-Bolshevik peace negotiations, the internal situation in Bolshevik Russia, and the international relations of Bolshevik Russia. The painted image covers the period from the signing of the peace preliminaries to the con-clusion of the peace treaty. It is examined from the perspective of the newspaper Robotnik (‘The Worker’).
p. 115-133
Summary in English.
Keywords: Robotnik (journal; Poland; 1894-1939); peace preliminaries; Treaty of Riga (1921); Bolshevik Russia